Recyclable amberlyst-70 as a catalyst for biginelli reaction: an efficient one-pot green protocol for the synthesis of 3,4-dihydropyrimidin-2(1H)-ones - Chandak, Hemant S.; Lad, Nitin P.; Upare, Pravin P. (Catalysis Letters, 2009)
An environmentally benign aqueous protocol for the synthesis of 3,4-dihydropyrimidin-2(1H)-ones using Amberlyst-70 as a recyclable catalyst has been developed. The use of resinous, nontoxic, thermally stable and inexpensive Amberlyst-70, as a recyclable heterogeneous catalyst, makes the process simple with negligible chemical waste. Thus renders this method an environmentally acceptable synthetic tool for Biginelli reaction.
Keywords: Amberlyst-70; Biginelli reaction; green chemistry; heterogeneous catalysis

Environmentally benign synthesis of beta-hydroxy sulfides using cyclic carbonates catalyzed by large-pore zeolites - Upare, Pravin P.; Kinage, Anil K.; Shingote, Savita K.; Gupte, Sunil P. (Green Chemistry Letters and Reviews, 2012)
An efficient one-pot synthesis of beta-hydroxy sulfides from thiophenol and cyclic carbonates catalyzed by large-pore zeolites has been reported. Reaction of thiophenol with ethylene carbonate in the presence of the Na-X zeolite catalyst gave the highest yield of 2-(phenylthio)ethanol (100%), while reaction with propylene carbonate a highest yield of regioselective product 1-(phenylthio)propan-2-ol was obtained (97%). Enantiomerically pure 1,2-propylene carbonate gave highly regioselective and stereospecific phenylthiopropanol, demonstrating that original chirality of propylene carbonate is retained. A plausible mechanism has been proposed for zeolite-catalyzed transformation involving a chemoselective nucleophilic attack of thiophenoloxide ion onto the less-substituted carbon of cyclic carbonate. The Na-X zeolite catalyst is recyclable and provides advantages of green chemistry approach to the synthesis of beta-hydroxy sulfides without the use of any solvent.
Keywords: beta-hydroxy sulfide; ethylene carbonate; propylene carbonate; thiophenol; zeolite